Dementia with dignity - Stammer, Kay; Eastway Communication; Media One. (Australia : Media One, 2006)
Geared for both professional and family caregivers, this shows how the quality of life for persons with dementia can be enhanced. Understand the various effects of dementia, learn how to communicate and respond to the specialized needs of the person behind the illness, and strengthen and encourage use of the remaining skills the person has in order to build self-esteem and stimulate intellectual abilities.
Title from title screen.
Based on Barbara Sherman's best selling book.
Executive producer, John Eastway ; editor, Michael E. Beer ; sound, Sam Humphries, Tim Parratt ; photography, Paul Ree.
Narration: Kay Stammers.
DVD format.
Keywords: Dementia